A Phenomenological Pre- and Post-Reflective Comparison of Graduate Student Intercultural Competence from Agricultural Service-Learning Experiences - Kim E Dooley; Catherine E. Sanders; Leslie Edgar (Journal of International Agricultural and Extension Education, 2023)
The purpose of this study was to determine growth in intercultural competence after graduate students participated in an international service learning (ISL) experience. One method for developing intercultural competence is service learning, where students apply learning in real-world settings through a cycle of action and reflection. This study used an interpretative phenomenological analysis related to the lived experience of eight graduate students who participated in two intensive ISL projects in Timor-Leste or Guatemala. Results included the student point of view (emic) narrative as an ethnographic crafted profile for each participant to demonstrate the process of intercultural competence development across individual and interaction processes. Students demonstrated knowledge gains after the experience, and several internal and external outcomes in their post-reflective narratives. Despite visiting different countries, the two groups of students demonstrated similar intercultural outcomes along the theoretical framework, indicating that despite contextual differences in experience, this framework maintains a robust perspective for analysing student experiences during ISL. The Process Model of Intercultural Competence served as a framework to assess intercultural competence. The process began with personal attitudes, openness to intercultural learning, and curiosity. Interpersonal outcomes developed with knowledge/comprehension through skills such as listening, observing, and interpretation. Developing flexibility, empathy, and adaptability promoted an informed frame of reference for a desired internal outcome. The external outcome resulted in behaving and communicating effectively from experience. Measuring intercultural diversity as a learning outcome from ISL can ensure adequate preparation for international development professionals.
Keywords: international service learning; preflection; intercultural competence; reflection; learning outcomes